2020
DOI: 10.3389/fnins.2020.575081
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor Functional Connectivity: A Neurophysiological Factor Related to BCI Performance

Abstract: Brain-Computer Interfaces (BCIs) are systems that allow users to control devices using brain activity alone. However, the ability of participants to command BCIs varies from subject to subject. About 20% of potential users of sensorimotor BCIs do not gain reliable control of the system. The inefficiency to decode user's intentions requires the identification of neurophysiological factors determining “good” and “poor” BCI performers. One of the important neurophysiological aspects in BCI research is that the ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 74 publications
4
37
0
Order By: Relevance
“…In addition, Lee et al (2020) observed significantly higher effective connectivity from the supplementary motor area (SMA) to the right dorsolateral prefrontal cortex (DLPFC) in high aptitude BCI users during resting-state when compared to low aptitude performers. Implementing these findings, research showed that functional connectivity during the MI task (Yi et al, 2014;Stefano Filho et al, 2017;Gu et al, 2020;Vidaurre et al, 2020;etc. ) or the change in functional connectivity from resting-state to MI task can be used as a feature for MI-BCI classification (Gonuguntla et al, 2016;Hamedi et al, 2016).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…In addition, Lee et al (2020) observed significantly higher effective connectivity from the supplementary motor area (SMA) to the right dorsolateral prefrontal cortex (DLPFC) in high aptitude BCI users during resting-state when compared to low aptitude performers. Implementing these findings, research showed that functional connectivity during the MI task (Yi et al, 2014;Stefano Filho et al, 2017;Gu et al, 2020;Vidaurre et al, 2020;etc. ) or the change in functional connectivity from resting-state to MI task can be used as a feature for MI-BCI classification (Gonuguntla et al, 2016;Hamedi et al, 2016).…”
Section: Introductionmentioning
confidence: 91%
“…In the former studies, both effective connectivity (e.g., Lee et al, 2020) and functional connectivity (e.g., Vidaurre et al, 2020) measures have been investigated, however, these studies employed various metrics of connectivity including coherence, phase synchronization, phase-slope index, etc., which employ different algorithms and hence vary in their interpretation (Bastos and Schoffelen, 2016). However, to fully tackle the disadvantages of EEG, such as artifacts and inter-trial/inter-subject amplitude variability, phase-based relationships (e.g., phase synchronization) might provide the best functional connectivity measure of spatially distributed regions that are active during mental task execution (Caicedo-Acosta et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been recognized earlier as a major challenge for studying phase-amplitude coupling (PAC) in neuronal data (Aru et al, 2015;Giehl et al, 2021;Jensen et al, 2016;Lozano-Soldevilla et al, 2016;Zhang et al, 2021) as well as for n:m phase-synchronization (Hyafil, 2017;Scheffer-Teixeira and Tort, 2016;Siebenhühner et al, 2020). In this work, we directly addressed the issue of spurious interactions due to waveshape of oscillations and offer a solution for the assessment of phase synchronization as one of the most important measures used for connectivity analyses with brain electrophysiology (Marzetti et al, 2019;Nentwich et al, Sadaghiani et al, 2021;Vidaurre et al, 2020). Currently available measures for quantifying n:m phase-synchronization (also referred to as cross-frequency synchronization -CFS) are not suitable for differentiation between genuine and spurious interactions.…”
Section: Discussionmentioning
confidence: 99%
“…A solid reason for BCI illiteracy is that subjects with poor control performance do not exhibit discriminative task-related changes over the modulation of Sensorimotor Rhythms (SMR) within the resting-state as well as in the interval of MI responses [11]. In particular, BCI faces real-world challenges, which are mostly caused by the low spatial resolution of EEG that, along with the nonstationarity present in the recorded neurophysiological signals, results in a poor signal-to-noise ratio (SNR).…”
Section: Introductionmentioning
confidence: 99%